POSSIBLE DIRECTIONS OF CHANGE OF KEY SEGMENTS OF THE ECONOMIC REGULATORY FRAMEWORK IN SERBIA - Gojko M. Rikalović; Dejan S. Molnar (Acta Economica, 2019)
The paper first analyzes the institutional framework of the economy and public finances in Serbia, with particular reference to the treatment of the SME sector and entrepreneurs, foreign investors and the digital (IT) infrastructure. A special part of the paper deals with the dynamics of accession to the European Union of some countries that are now members of this integration, as well as with the process of Serbia’s membership, since it is considered that this process is the key determinant of the institutional conditions for our country. The third part deals with the treatment of public finances in the Constitutions of the selected EU Member States.